Synthesis and In Vitro/In Vivo Evaluation of Hypoxia-Enhanced (111)In-Bombesin Conjugates for Prostate Cancer Imaging - Zhou, Zhengyuan (2013)
Receptor-targeted agents, such as BB2r-targeted peptides, have been investigated extensively in preclinical and clinical studies. In an attempt to increase the effectiveness of diagnostic and/or radiotherapeutic agents, we have begun to explore the incorporation of the hypoxia-selective prodrug 2-nitroimidazole into receptor-targeted peptides. Hypoxia is a well-known characteristic of many solid tumors, including breast, prostate and pancreatic cancers. The aim of this approach is to utilize the hypoxia trapping capability of 2-nitroimidazoles to increase the retention of the agent in hypoxic, BB2r-positive tumors. We have demonstrated that incorporation of one or more 2-nitroimidazoles into the BB2r-targeted peptide significantly increases the in vitro retention of the agent in hypoxic prostate cancer cells. The study described herein represents our first investigation of the in vivo properties of these hypoxia-enhanced BB2r-targeted agents in a PC-3 xenograft mouse model. METHOD: Four (111)In-labeled BB2r-targeted conjugates, (111)In-1, (111)In-2, (111)In-3 and (111)In-4, composed of 0–3 2-nitroimidazole moieties, respectively, were synthesized, labeled and purified. The BB2r binding affinities, externalization and protein association properties of these radioconjugates were assessed using the BB2r-positive PC-3 human prostate cancer cell line under hypoxic and normoxic environments. The in vivo biodistribution and microSPECT/CT imaging of the (111)In-1, (111)In-2 and (111)In-4 radioconjugates were investigated in PC-3 tumor bearing SCID mice. RESULTS: All conjugates and (nat)In-conjugates demonstrated nanomolar binding affinities. (111)In-1-4 demonstrated 41.4, 60.7, 69.1 and 69.4 % retention, correspondingly, of internalized radioactivity under hypoxic conditions relative to 34.8, 35.3, 33.2 and 29.7 % retention under normoxic conditions. Protein-association studies showed significantly higher levels of association under hypoxic conditions for 2-nitroimidazole containing BB2r-targeted radioconjugates compared to control. Based on the initial 1 hour uptake in the PC-3 tumors, (111)In-1, (111)In-2 and (111)In-4 demonstrated tumor retentions of 1.5, 6.7 and 21.0%, respectively, by 72 h post-injection. Micro-SPECT/CT imaging studies of (111)In-1, (111)In-2 and (111)In-4 radioconjugates resulted in clear delineation of the tumors. CONCLUSION: Based on the in vitro and in vivo studies, the BB2r-targeted agents that incorporated 2-nitroimidazole moieties demonstrated improved retention. These results indicate that further exploration into the potential of hypoxia-selective trapping agents for BB2r-targeted agents, as well as other targeted compounds, is warranted.